Hormone replacement therapy and risk of epithelial ovarian cancer - Purdie, D M (Nature Publishing Group, 1999)
It has been suggested that oestrogen replacement therapy is associated with risk of epithelial ovarian cancer of the endometrioid type. Using data from an Australian population-based case–control study, the relation between unopposed oestrogen replacement therapy and epithelial ovarian cancer, both overall and according to histological type, was examined. A total of 793 eligible incident cases of epithelial ovarian cancer diagnosed from 1990 to 1993 among women living in Queensland, New South Wales and Victoria were identified. These were compared with 855 eligible female controls selected at random from the electoral roll, stratified by age and geographic region. Trained interviewers administered standard questionnaires to obtain detailed reproductive and contraceptive histories, as well as details about hormone replacement therapy and pelvic operations. No clear associations were observed between use of hormone replacement therapy overall and risk of ovarian cancer. Unopposed oestrogen replacement therapy was, however, associated with a significant increase in risk of endometrioid or clear cell epithelial ovarian tumours (odds ratio (OR) 2.56; 95% confidence interval (CI) 1.32–4.94). In addition, the risk associated with oestrogen replacement therapy was much larger in women with an intact genital tract (OR 3.00; 95% Cl 1.54–5.85) than in those with a history of either hysterectomy or tubal ligation. Post-menopausal oestrogen replacement therapy may, therefore, be a risk factor associated with endometrioid and clear cell tumours in particular. Additionally, the risk may be increased predominantly in women with an intact genital tract. These associations could reflect a possible role of endometriosis in the development of endometrioid or clear cell ovarian tumours. © 1999 Cancer Research Campaign